Europec/Eage Conference and Exhibition 2008
DOI: 10.2118/113647-ms
|View full text |Cite
|
Sign up to set email alerts
|

Control-Relevant Upscaling

Abstract: The conventional reason for upscaling in reservoir simulation is the computational limit of the simulator. However, we argue that, from a system-theoretical point of view, a more fundamental reason is that there is only a limited amount of information (output) that can be observed from production data, while there is also a limited amount of control (input) that can be exercised by adjusting the well parameters; in other words, the input-output behavior is usually of much lower dynamical order than the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…It has been shown that it is also possible to make use of spatial correlations in the states (pressures, saturations) to reduce the order of reservoir models using system-theoretical techniques, but application of these possibilities in optimization, data assimilation or upscaling has hardly yet been pursued. For some early attempts, see Heijn et al (2004), Van Doren et al (2006, Markovinović and Jansen (2006), Gildin et al (2006), Vakili-Ghahani et al (2008 and Cardoso et al (2008).…”
Section: Reparameterization and Model Reductionmentioning
confidence: 99%
“…It has been shown that it is also possible to make use of spatial correlations in the states (pressures, saturations) to reduce the order of reservoir models using system-theoretical techniques, but application of these possibilities in optimization, data assimilation or upscaling has hardly yet been pursued. For some early attempts, see Heijn et al (2004), Van Doren et al (2006, Markovinović and Jansen (2006), Gildin et al (2006), Vakili-Ghahani et al (2008 and Cardoso et al (2008).…”
Section: Reparameterization and Model Reductionmentioning
confidence: 99%